2022
DOI: 10.3389/fnbeh.2022.798375
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Event-Related Desynchronization Observed During Volitional Swallow by Electroencephalography Recordings in ALS Patients With Dysphagia

Abstract: Dysphagia is a severe disability affecting daily life in patients with amyotrophic lateral sclerosis (ALS). It is caused by degeneration of both the bulbar motor neurons and cortical motoneurons projecting to the oropharyngeal areas. A previous report showed decreased event-related desynchronization (ERD) in the medial sensorimotor areas in ALS dysphagic patients. In the process of degeneration, brain reorganization may also be induced in other areas than the sensorimotor cortices. Furthermore, ALS patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 43 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…Significant ERDs were observed in multiple cortical areas during volitional swallowing but in spatial distributions that were different from the ERDs of healthy subjects. All patients showed cortical activation in both frontal areas involved in a cognitive effort during swallowing 19 ) and sensorimotor areas that were active in voluntary swallowing in healthy people, 18 ) although the distribution was different for each case. These patterns of cortical activation after total laryngectomy might suggest the existence of divergent and multiple paths of neural recovery processes among individuals with swallowing dysfunction.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Significant ERDs were observed in multiple cortical areas during volitional swallowing but in spatial distributions that were different from the ERDs of healthy subjects. All patients showed cortical activation in both frontal areas involved in a cognitive effort during swallowing 19 ) and sensorimotor areas that were active in voluntary swallowing in healthy people, 18 ) although the distribution was different for each case. These patterns of cortical activation after total laryngectomy might suggest the existence of divergent and multiple paths of neural recovery processes among individuals with swallowing dysfunction.…”
Section: Discussionmentioning
confidence: 97%
“…35) We have also found ERD in the prefrontal area during volitional swallowing in ALS patients with dysphagia with decreased swallowing pressure. 19) Given that the patient in Case 3 also reported that he made no effort in swallowing, ERD in the prefrontal area may reflect unconscious cognitive process 44,45) to achieve more forceful tongue movements with decreased propulsion after removal of the pharyngeal muscles. The superior premotor area and the bilateral medial somatosensory areas also showed significant ERD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations